Are emotions essential for consumer ethical decision-making: A necessary condition analysis - Escadas, M. (2024)
This research examines the necessary condition of emotions in predicting consumer ethical decision-making, using a new multiplicative method for identifying and measuring the necessary condition in data sets—Necessary Condition Analysis (NCA). Based on a sample of over four hundred individuals, and combining three different consumption scenarios involving ethical issues, our findings demonstrate that emotions are a necessary condition for consumer ethical decisions and behaviours. In addition, the results show that higher levels of consumer ethical decisions can only be achieved if happiness, gladness and satisfaction increase towards a minimum level of necessity. The findings provide empirical support for the essential role of emotions in predicting consumer ethical decision-making. Furthermore, this research identifies the emotional thresholds without which ethical choices cannot occur and then explains why individuals sometimes behave ethically but other times do not. In addition, this is a first contribution applying NCA to consumer ethics.